Aktivitas Antibakteri Ekstrak Daun Mangga Sengir (Mangifera indica L. Kultivar Sengir) terhadap Staphylococcus aureus: Studi In vitro dan Molecular Docking - Yusrin Haniyyah; Md. Sanower Hossain (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The antibacterial potential of the underexplored Mangifera indica L. cultivar Sengir remains poorly understood. This study evaluated the antibacterial activity of Sengir mango leaf extract against Staphylococcus aureus using integrated in vitro and in silico approaches. Leaves were extracted by maceration with 70% ethanol. The extract contained 293.8 mg GAE/g extract of total phenolics and 34.8 mg QE/g extract of total flavonoids. Antibacterial activity was assessed using the disk diffusion method at extract concentrations of 40%, 60%, 80%, and 100%, corresponding to 488, 732, 976, and 1,220 mg/mL, respectively. Ampicillin and 10% DMSO served as the positive and negative control, respectively. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were also determined. For the in silico study, 60 M. indica phytochemicals from IMPPAT were screened using SwissADME and ProTox-III, and seven compounds were docked against penicillin-binding protein 2a (PBP2a; PDB ID: 4CJN) using PyRx. The extract produced concentration-dependent inhibition zones of 11.00–17.17 mm, whereas ampicillin produced a 34.50 mm inhibition zone and 10% DMSO showed no inhibition. MIC and MBC values were 48.87 and 73.20 mg/mL, respectively. Guaiol showed the lowest predicted binding energy (-7.0 kcal/mol), whereas PASS analysis identified Pogostol, Myrtenyl acetate, and Bicyclogermacrene as potential antibacterial compounds. Overall, Sengir mango leaf extract showed antibacterial activity against S. aureus, while computational analysis identified Guaiol and Pogostol as promising bioactive candidates for further validation.